Template for uniform reporting of emergency department measures, consensus according to the Utstein method. (December 2019) - Hruska, Katrin; Castrén, Maaret; Banerjee, Jay; Behringer, Wilhelm; Bjørnsen, Lars P.; Cameron, Peter; Einav, Sharon; Holroyd, Brian R.; Jones, Peter; Lassen, Annmarie; Truesdale, Melinda; Kurland, Lisa
Abstract : Objective: To develop a template for uniform reporting of standardized measuring and describing of care provided in the emergency department (ED). Methods: An international group of experts in emergency medicine, with broad experience from different clinical settings, met in Utstein, Norway. Through a consensus process, a limited number of measures that would accurately describe an ED were chosen and a template was developed. Results: The final measures to be reported and their definitions were grouped into six categories: Structure, Staffing and governance, Population, Process times, Hospital and healthcare system and Outcomes. The template for Utstein-style uniform reporting is presented. Conclusion: The suggested template is intended for use in studies carried out in EDs to improve comparability and knowledge translation. Abstract : Supplemental Digital Content is available in the text.